Changes in Zinc Transporter 8 Autoantibodies Following Type 1 Diabetes Onset: The Type 1 Diabetes Genetics Consortium Autoantibody Workshop - Wenzlau, Janet M. (Diabetes Care, 2015)
Zinc transporter 8 autoantibodies (ZnT8A) were analyzed in sera from 1,504 subjects as part of the Type 1 Diabetes Genetics Consortium (T1DGC) Autoantibody Workshop. For these participants with type 1 diabetes (T1D), samples were collected within 3 years of T1D diagnosis. ZnT8A were detected in 862 subjects (57.3%), with the highest frequencies and median titers being associated with the shortest duration of disease. ZnT8A were present at similar frequencies in non-Hispanic whites, non-Hispanic blacks, and Hispanics, but significantly less prevalent in those of Asian ancestry. Sera containing ZnT8A selectively recognizing at least one of the SLC30A8 single nucleotide polymorphisms (encoding ZnT8A) were detected in all populations; however, Trp-specific sera were much less frequent in non-Hispanic blacks, consistent with the anticipated lower frequency of the SLC30A8 rs13266634 T allele in African American populations. ZnT8A positivity was associated with HLA-DQ8, but this was primarily due to the DRB1*0404-DQ8 haplotype. This was in contrast to autoantibodies to IA-2 that were strongly associated with DRB1*0401-DQ8. These effects appeared essentially independent of racial or ethnic background. The DRB1*0401-DQ8 and DRB1*0404-DQ8 haplotypes were associated with T1D subjects positive for GAD65, IA-2, and ZnT8A. In contrast to DRB1*0401-DQ8, there was no significant association of DRB1*0404-DQ8 with single or dual autoantibody positivity. The DRB1*0404-DQ8 haplotype was also associated with T1D subjects whose sera recognized both polymorphic variants of zinc transporter 8, an effect not seen for DRB1*0401-DQ8.